Sharia Economic Dispute Resolution Through Mediation: Between Fast Basics and Justice for Clients - Maria Rosalina; M Pratama Siagian; M Rafi Akbar Sitakar; M Alfareza Siregar (Pancasila and Civics Education Journal (PCEJ), 2026)
Abstract: This study analyses the tension between the principles of speed, simplicity, and low cost in the mediation of Islamic economic disputes and the need to ensure substantive justice for customers. The rapid expansion of the Islamic financial sector in Indonesia has been accompanied by an increase in Islamic economic disputes, prompting Religious Courts, which hold absolute jurisdiction under Law Number 3 of 2006 and Constitutional Court Decision Number 93/PUU-X/2012, to optimize mediation as a dispute resolution mechanism. Supreme Court Regulation Number 1 of 2016 requires mediation before substantive case examination to promote efficient and peaceful settlement. However, the implementation of the speed principle often encounters challenges arising from unequal bargaining positions between customers and Islamic financial institutions. As a result, mediation agreements may fulfill procedural requirements while failing to provide meaningful substantive justice. This research employs a normative legal method using statutory and conceptual approaches, supported by qualitative descriptive-analytical analysis. The findings indicate that the speed principle has dual implications: it improves dispute resolution efficiency but may also weaken justice for customers with limited legal capacity. Key obstacles include the absence of customer-oriented mediation regulations, the limited number of mediators with expertise in Islamic economic law, and low public legal literacy. Strengthening customer protection, enhancing mediator competence, and improving legal literacy are essential to ensure fair and effective mediationKeywords: Mediation, Islamic Economic Dispute, Speed Principle, Substantive Justice, Customer Protection, Religious CourtAbstrak: Studi ini menganalisis ketegangan antara prinsip kecepatan, kesederhanaan, dan biaya rendah dalam mediasi sengketa ekonomi Islam dan kebutuhan untuk memastikan keadilan substantif bagi nasabah. Ekspansi pesat sektor keuangan Islam di Indonesia telah disertai dengan peningkatan sengketa ekonomi Islam, mendorong Pengadilan Agama, yang memiliki yurisdiksi absolut berdasarkan Undang-Undang Nomor 3 Tahun 2006 dan Keputusan Mahkamah Konstitusi Nomor 93/PUU-X/2012, untuk mengoptimalkan mediasi sebagai mekanisme penyelesaian sengketa. Peraturan Mahkamah Agung Nomor 1 Tahun 2016 mensyaratkan mediasi sebelum pemeriksaan kasus substantif untuk mendorong penyelesaian yang efisien dan damai. Namun, implementasi prinsip kecepatan seringkali menghadapi tantangan yang timbul dari posisi tawar yang tidak setara antara nasabah dan lembaga keuangan Islam. Akibatnya, perjanjian mediasi mungkin memenuhi persyaratan prosedural tetapi gagal memberikan keadilan substantif yang berarti. Penelitian ini menggunakan metode hukum normatif dengan pendekatan hukum dan konseptual, didukung oleh analisis deskriptif-analitis kualitatif. Temuan menunjukkan bahwa prinsip kecepatan memiliki implikasi ganda: meningkatkan efisiensi penyelesaian sengketa tetapi juga dapat melemahkan keadilan bagi nasabah dengan kapasitas hukum yang terbatas. Kendala utama meliputi tidak adanya regulasi mediasi yang berorientasi pada pelanggan, terbatasnya jumlah mediator yang memiliki keahlian dalam hukum ekonomi Islam, dan rendahnya literasi hukum masyarakat. Memperkuat perlindungan pelanggan, meningkatkan kompetensi mediator, dan meningkatkan literasi hukum sangat penting untuk memastikan mediasi yang adil dan efektifKata Kunci: Mediasi, Sengketa Ekonomi Islam, Prinsip Kecepatan, Keadilan Substansial, Perlindungan Konsumen, Pengadilan Agama